2011
DOI: 10.1111/j.1439-0396.2011.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Production performance, stress tolerance and intestinal integrity of sunshine bass fed increasing levels of soybean meal

Abstract: Soybean meal (SBM) is perhaps the most common fish meal (FM) alternative used in aquafeeds; however, SBM cannot fully replace FM in sunshine bass Morone chrysops × M. saxatilis feeds without impacting growth. Reduced production performance may be the result of subtle changes in morphology and/or physiological status. Accordingly, our objective was to assess growth, gastrointestinal integrity and stress tolerance of sunshine bass fed increasing amounts of SBM. Fish (approximately 14.5 g) were fed diets (14% lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…Success using fish meal–free feeds is rarely reported in cobia, and only in feeds containing relatively complex blends of ingredients and some animal‐derived proteins (Salze et al., 2010). In addition to the effects on production performance, marine protein replacement has been linked with reduced stress tolerance and increased handling mortality in other carnivorous taxa such as hybrid striped bass Morone chrysops × Morone saxatilis (Laporte and Trushenski, 2011; H.A. Lewis and J.T.…”
Section: Introductionmentioning
confidence: 99%
“…Success using fish meal–free feeds is rarely reported in cobia, and only in feeds containing relatively complex blends of ingredients and some animal‐derived proteins (Salze et al., 2010). In addition to the effects on production performance, marine protein replacement has been linked with reduced stress tolerance and increased handling mortality in other carnivorous taxa such as hybrid striped bass Morone chrysops × Morone saxatilis (Laporte and Trushenski, 2011; H.A. Lewis and J.T.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on sea bream showed that the replacement of dietary fish oil with vegetable oils (such as linseed oil, but not soybean oil) led to significantly higher plasma cortisol concentrations after acute stress , and significantly higher levels of cortisol release by the head kidney after adrenocorticotropic hormone (ACTH) stimulation (Ganga et al 2011). Similar results have also been shown in sunshine bass (Morone saxatilis) and cobia (Rachycentron canadum) fed reduced fish meal feeds (Laporte and Trushenski 2012;Trushenski et al 2013). The replacement of fish oil with vegetable oils devoid of LC-PUFA results in lower tissue concentrations of arachidonic acid, essential fatty acids and DHA (Ganga et al 2011).…”
Section: Physiological Traitsmentioning
confidence: 56%
“…The distal intestines of cobia (Rachycentron canadum) (Romarheim et al, 2008), Egyptian sole (Solea aegyptiaca) (Bonaldo et al, 2006), and European seabass (Bonaldo et al, 2008) were completely unaffected by feeding soybean meal. Similarly, the intestinal integrity of hybrid striped bass (Morone chrysops x M. saxatilis) was largely unaffected by feeding soybean meal, soy protein concentrate, or soy protein isolate (Blaufuss and Trushenski, 2012;Laporte and Trushenski, 2012). Gilthead seabream exhibited only minor infiltration of leukocytes into the lamina propria of the distal intestine (Bonaldo et al, 2008).…”
Section: Antinutritional Factors and Gut Healthmentioning
confidence: 93%